Balancing Numbers and Application - Gautam, Ramesh (Journal of Advanced College of Engineering and Management, 2018)
In this paper, we present about origin of Balancing numbers; It!s connection with Triangular, Pells numbers, and Fibonacci numbers; beginning with connections of balancing numbers with other numbers system, It elaborate the different generating functions of balancing numbers. It also include some amazing recurrence relations; and the application of balancing numbers in solving Diophantine equation.